Ecological and demographic correlates of helping behaviour in a cooperatively breeding bird. (24th January 2013) - Hatchwell, Ben J.; Sharp, Stuart P.; Beckerman, Andrew P.; Meade, Jessica; Wright, Jonathan
Summary The evolution of cooperation is a persistent problem for evolutionary biologists. In particular, understanding of the factors that promote the expression of helping behaviour in cooperatively breeding species remains weak, presumably because of the diverse nature of ecological and demographic drivers that promote sociality. In this study, we use data from a long‐term study of a facultative cooperative breeder, the long‐tailed tit Aegithalos caudatus, to investigate the factors influencing annual variation in helping behaviour. Long‐tailed tits exhibit redirected helping in which failed breeders may become helpers, usually at a relative's nest; thus, helping is hypothesised to be associated with causes of nest failure and opportunities to renest or help. We tested predictions regarding the relationship between annual measures of cooperative behaviour and four explanatory variables: nest predation rate, length of the breeding season, population‐level relatedness and population density. We found that the degree of helping was determined principally by two factors that constrain successful independent reproduction. First, as predicted, cooperative behaviour peaked at intermediate levels of nest predation, when there are both failed breeders (i.e. potential helpers) and active nests (i.e. potential recipients) available. Second, there were more helpers in shorter breeding seasons when opportunities for renesting by failed breeders are more limited. These are novel drivers of helping behaviour in avian cooperative breeding systems, and this study illustrates the difficulty of identifying common ecological or demographic factors underlying the evolution of such systems.